Aplikasi Pupuk Kandang dan Pupuk SP-36 Untuk Meningkatkan Unsur Hara P Dan Pertumbuhan Tanaman Jagung (Zea mays L.) di Tanah Inceptisol Kwala Bekala - Hazrianda Muda Siregar; Jamila Jamilah; Hamidan Hanum (Jurnal Agroekoteknologi, 2015)
The objective this research was to know the effect of application phosphorus fertilizer and farmyard manure on improvement of phosphorus availability and uptake and growth of maize on Inceptisol which taken from Kwala Bekala North Sumatera. The research was conducted in the screen house and Chemical and Soil Fertility Laboratory, Faculty of Agriculture, University of North Sumatra on Februari-Juli 2014. This study used randomized block designed which consisted of 2 factors and 3 replications. The first factor which consisted Farmyard manure: 1. (control) 2. chicken manure, 3. Cow manure, 4. sheep manure. The seconds factor SP-36 which consisted of 4 levels: 0, 50, 100 and 150 kg SP-36/ha. The results showed interaction of SP-36 fertilizer application and farmyard manure significantly increased the C-organic, P-available, P plant uptake and growth plants. Chicken manure and with 150 kg SP-36/ha afford to increase P plant uptake just than the others. Farmyard manure could decrease SP-36 dosage.Keywords: SP - 36 fertilizer , farmyard manure , soil P - available